DECONSTRUCTING THE POLICIES FOR INDIA’S NORTH-EAST: UNDERSTANDING IDENTITY, ETHNICITY AND SUB-NATIONALISM - Mehta, Subhash; Prakash, Aditya (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The Look East Policy of 1991 and the rechristened Act East policy of 2014 are designed to have greater ties with India’s neighbours to the east, especially South-east Asia and the Indo-Pacific region. While the ‘Look-East’ policy was designed to foster economic ties with India’s neighbours surrounding the North-East region and address India’s neglect of the Southeast Asian region, especially during the Cold War. The ‘Act-East’ policy was formulated to expand these ties to add deeper defence and security cooperation with the same neighbours and cover a wider Indo-Pacific region. ‘The North-East’ region is the playground for these experimentation and implementation of policies. This development has changed the dynamics of the region in terms of land rights, displacement, resource extraction, demographics and socio-cultural relations including difficulty in deconstructing the matrix of class and ethnicity in the north-east region. This paper will try to understand the dynamics of development policies and their counter effects on the aspects of identity, ethnicity and sub-nationalism in the north-eastern region of India. It will also understand the after effects of the policy on the crisis of labour markets, migrant workers and will try to study, analyse and understand the existing schisms and limitations in the approach of implementation of government policies in the north-eastern region.